ОСНОВЫ ИДЕОГРАФИЧЕСКОГО ОПИСАНИЯ СОМАТИЧЕСКИХ (на материале романа З.Сәмәди «Истәк вә қисмәт») - Курванбакиева, А. Н. (Journal of Oriental Studies, 2016)
Novel З. The "Fate and desire" of Samadhi is the last of novels in its creativity. Consideration of somatic phraselogical units represents rich material for studying of outlook of the Uyghur nations. The analysis of given units promoted revealing of communication of somatic phraseological units with the person, its ability to live. Белгілі ұйғыр жазушысы З.Самадидің «Тілек пен жазмыш» атты романы оның соңғы шығармасы болып табылады. Бұл мақала адамның дүниетанымынан, оның ішкі рухани дүниесінен көріністер беретін соматикалық фразеологизмдерді қарастыруға арналған.